Teacher’s Perspective on the Modular System of Education - A Study on Government Medical College Teachers and Their Views on Educational Systems (Medical Forum Monthly, 2024)
Objective: To assess the level of satisfaction about different systems among medical college teachers. To compare their preference among the modular and annular system and to assess percentage of faculty in favor of reverting back to old system.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the Department of Community Medicine, SMC, JSMU, Karachi from January to May 2016.Materials and Methods: A study was conducted on a sample of 122 teachers from 3 government medical colleges (DMC, SMC and DIMC). Of these, 65 were male and 57 were female. From DMC 52, SMC 43 and DIMC 27 teachers participated in filling the questionnaire. The sample was taken through Non-Probability Purposive sampling from the three medical colleges. An informed verbal consent was taken from the candidates. Pilot study was conducted to assess the authenticity of the questionnaire. A structured questionnaire was then distributed, got filled, data was entered and analyzed using SPSS version 21, with 95% confidence interval and 0.05 p-value. Results: A total of 122 teachers from 3 government medical colleges (DMC, SMC and DIMC) were asked to fill the questionnaire. From the total teachers 54.7% believed that modular system focused more on theoretical learning while 42.6% said that it focused on practical learning. 72.6% of teachers said that modular system is more stressful compared to 27.04% who disagreed. 51.6% said that the stress affected their teaching and 48.4% said otherwise. 91% teachers said that there was a need that teachers should be trained on how to teach according to the modular system while 9% said there was no need for training the teachers. 62.3% teachers said that the modular system did not allocate enough time to each subject as allotted by PMDC while 37.7% disagreed. 69.3% teachers said that the annual system gives sufficient time to each subject per PMDC guidelines while 30.7% disagreed. 64.8% teachers said that their institute should revert back to annual system of teaching while 35.2% disagreed. 64.8% teachers chose ‘annual system’ as their preferred system of education while 35.2% opted for the ‘modular system’.Conclusion: The study concluded that the teachers of government medical colleges where module system has been implemented would like their institutions to revert back to the ‘annual system’ of teaching, declaring the latter their preferred system of teaching. They believed that the modular system was more stressful and focuses more on theoretical learning rather than practical learning.